Answer:
(3, 2)
x= 3
y= 2
Step-by-step explanation:
[tex]4x+7y=26\\4x-5y=2[/tex]
You have to cancel out one of the variables. In this case I am canceling out 4x. I'm doing that by multiplying all the numbers in that equation by -1 because 4x is positive and I'm doing the inverse property of it.
[tex]-1*(4x+7y=26)\\4x-5y=2[/tex]
Now you have your new equation.
[tex]-4x-7y=-26\\4x-5y=2[/tex]
Next, you have to add the two equations together.
[tex]-12y=-24[/tex]
You divide -12 by -24 and you get 2.
[tex]y=2[/tex]
Now you have to substitute 2 to find out what x is. You can pick any equation to substitute with.
[tex]4x+7y=26\\4x+7(2)=26[/tex]
Then you solve it to find x.
[tex]4x+7(2)=26\\4x+14=26\\4x=12\\x=3[/tex]
Your final answer for x should be 3. To conclude, y= 2 and x= 3.